2023
DOI: 10.1039/d2fd00123c
|View full text |Cite
|
Sign up to set email alerts
|

What stress components drive mechanochemistry? A study of ZDDP tribofilm formation

Abstract: Zinc diakyldithiophosphate (ZDDP), the most widely used antiwear additive in engine oils, has been extensively studied over the last few decades to help understand the origin of its effectiveness. Glassy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…To apply this model, the mean p in the nanoreactor contacts was determined as a function of F by dividing by the feature area. Our use of mean pressure is consistent with current published work on probe-based mechanochemistry ( 32 , 49 , 50 ). There was a spatial distribution of that pressure, as seen in our finite element simulations (fig.…”
Section: Determination Of Activation Parameterssupporting
confidence: 88%
“…To apply this model, the mean p in the nanoreactor contacts was determined as a function of F by dividing by the feature area. Our use of mean pressure is consistent with current published work on probe-based mechanochemistry ( 32 , 49 , 50 ). There was a spatial distribution of that pressure, as seen in our finite element simulations (fig.…”
Section: Determination Of Activation Parameterssupporting
confidence: 88%
“…Previous experiments have shown that tribofilm growth is primarily controlled by shear stress and not the normal stress. 9,10,91 Moreover, from Fig. 3c, it is clear that the higher shear stress in the 100% TCP system leads to larger k values than for the 50% TCP, 50% DIDA systems, even at identical normal stress (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…This reduction in shear stress is expected to due the lubricating effect of the low-friction ester base oil. 90 From previous mechanochemistry experiments of ZDDP tribofilm growth, 9,10,91 it is anticipated that the lower shear stress will result in lower reactivity for the 50% TCP, 50% DIDA than the 100% TCP system. Fig.…”
Section: Base Oil Effects On Tcp Decompositionmentioning
confidence: 99%
“…A recent study has demonstrated that the contact pressure can hinder tribo−chemical reactions. 46 Physically, the vapor phase lubricated friction likely involves the local mobility of groups of 2-propanol molecules. As the partial pressure of the vapor phase lubricant is increased, the "mobile" volume also increases, suggesting that larger clusters of 2-propanol become involved in the shear process, as illustrated in Figure 4D.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The energy required to activate the shear process, Q ′ , was found to be ∼1.0 × 10 –19 J or 0.6 eV for all lubrication conditions (Figure S4), a typical energy for bonding at the molecular scale. ,,, This energy contains the pressure-induced barrier, i.e., p Ω; this suggests that as pressure increases in the contact, the required energy for the shear event will become larger and, thus, hamper the sliding process. A recent study has demonstrated that the contact pressure can hinder tribo–chemical reactions . Physically, the vapor phase lubricated friction likely involves the local mobility of groups of 2-propanol molecules.…”
Section: Introductionmentioning
confidence: 99%